Analisis Regulasi Fintech dan Implikasinya Terhadap Operasional Bank Digital Dalam Studi Kasus Indonesia - Manggala, Bayu Suryadi; Mahendra, Rayhan Syahbana; Tambunan, Yesaya Geraldo; Nugroho, Andriyanto Adhi (Media Hukum Indonesia (MHI), 2024)
The development of financial technology has brought significant changes to the banking industry, especially with the emergence of financial technology (Fintech) and digital banks. This research examines the analysis of fintech regulations and their implications for digital bank operations in Indonesia. It focuses on the goal of identifying the impact of fintech regulations on digital banks as well as the legal challenges digital banks face in maintaining consumer data security. Through a normative juridical approach, this research examines related regulations, such as OJK Regulation No. 13/POJK.02/2018 concerning digital financial innovation and Bank Indonesia Regulation No. 19/12/PBI/2017 concerning the implementation of financial technology. The research results show that fintech regulations influence digital bank operations by creating a legal environment that impacts business models, operational strategies, and digital bank product innovation. Strict regulations, although aimed at increasing consumer confidence and preventing unhealthy financial practices, can limit the innovation and flexibility of digital banks. In addition, digital banks are faced with legal challenges regarding consumer data security, which require compliance with personal data protection regulations. This research provides important insights for regulators, digital banks, and related industry players to understand the complexity of fintech regulations and maintain a balance between technological innovation, data security, and consumer protection in the digital financial industry in Indonesia.